Endomarketing en las entidades promotoras de salud (EPS) de la ciudad de Barranquilla (2021)
The aim of this research was to analyze endomarketing in Health Promoting Entities (EPS) in the city of Barranquilla. The study was developed under a quantitative approach, descriptive type, of non-experimental design, having as a data collection technique the survey, which was applied to an intentional non-probabilistic sample of 21 collaborators, belonging to the 14 EPS that provide their services in the city. The collected responses were processed by means of a descriptive analysis in Microsoft Excel, yielding the data by means of absolute and relative frequency. Analyzing the results of the research, it was possible to analyze that the dimensions of endomarketing (internal communication, training and reward systems) are being used by the EPS for a better relationship with their collaborators. It was also possible to analyze that the consequences of endomarketing (organizational commitment, employee motivation and job satisfaction) registered mostly positive responses, taking into account that the percentage of variation of opinions within employees was minimal and that the responses were mostly in the positive alternatives for each item. It is concluded that the EPS are making endomarketing part of their processes in order to obtain happy collaborators and transmit solidity with external customers.